Valuation on an Outside-Reset Option with Multiple Resettable Levels and Dates. (8th April 2018) - Xue, Guangming; Qin, Bin; Deng, Guohe
Abstract : This paper studies an outside-reset option with multiple strike resets and reset dates, in which the strike price is adjusted by an external process associated with the underlying risky asset. We obtain analytical pricing formula for this option and the hedging parameters Delta and Gamma. Furthermore, some numerical examples are provided to analyze some characteristics of the outside-reset option and to examine the impacts of the external parameters on option prices and Greeks. These results show that the external process can significantly affect option prices and Greeks.